A formação e o desempenho profissional do professor - Leite, Alissandra Vaneli Nogueira (2009)
This paper aims to consider about the proposals for teacher training in Brazil since the creation of the first courses in Pedagogy. Then, it seeks to understand the evolution of legal devices, from the Public Policy Education, training courses for teachers and their reflection in the work professional performance. The methodological approach adopted is the document analysis, focused initially in the development process and implementation of educational laws, especially the LDB, which reveals considerable utopias in the proposals of teacher training. In the documentary analysis, the necessary data will be collected for the interpretation of the explicit and implicit meanings in the discussion. Finally, the paper aims to point to a possible understanding of an ideal training for the teacher and for a real identity construction of the education professional that is so devalued in our contemporary society.